Modelling the Composition and Structure of Campylobacter jejuni Biofilms - Dzianach, Paulina Agnieszka (Curtin University, 2020)
The goal of this research project was to study the effects of environmental and genetic factors on biofilm formation of Campylobacter jejuni with the use of mathematical modelling, experimental and bioinformatics techniques. Potential reasons for some puzzling observations regarding C. jejuni biofilm formation have been proposed as a result of this study, and a number of genes and SNPs have been identified, which may play a role in biofilm formation of this pathogen.